ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN LANGKAH-LANGKAH POLYA PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL KELAS VIII SMP ISLAM TUANKU LINTAU - Arnina Dwi Jaya (Jurnal Edukasi dan Penelitian Matematika, 2022)
Problem-solving ability is one aspect that is the main focus of learning. Students use the knowledge they already have to solve the problems given. One method of solving the problem is to use the Polya step, namely understanding the problem, planning a solution, implementing a settlement plan, and checking back. The low mathematical problem-solving ability of students is caused by the habits of students in solving problems according to what the teacher teaches and the lack of giving mathematical problem-solving questions which results in students lacking the skills to solve mathematical problem-solving ability questions. Based on these problems, the formulation of the problem of this research is how the mathematical problem-solving ability of students of Islamic Junior High School Tuanku Lintau on the material of variable equation system in terrms of Polya's steps. This study aims to describe and analyze students' ability to solve mathematical problems using Polya's steps on the material of a two-variable system of linear equations in class VIII SMP Islam Tuanku Lintau. The type of research being conducted is descriptive in nature, since the subjects of research are selected using a targeted sampling method. Tests and interviews were used as data collection methods, while the analytical methods used for this study were descriptive analysis and data triangulation. As a result, the average score of mathematical problem-solving ability in the problem understanding stage was 1.43, the average score in the calculation planning stage was 1.74, and the average score in the calculation plan execution stage was 1.43. 0.51 and in the verification step. Again the average score is 0.33. Therefore, the lowest average score is reviewed in the last step, and the highest average score is taken as the problem understanding step. Keywords– Problem-Solving, Polya's steps, two-variable system of linear equations